Role of Plasma Clusterin in Alzheimer’s Disease—A Pilot Study in a Tertiary Hospital in Northern India - Vishnu, Venugopalan Y. (PLoS One, 2016)
OBJECTIVE: To evaluate the role of plasma clusterin in Alzheimer’s disease (AD). BACKGROUND: Plasma clusterin is a promising biomarker as various studies have shown it to be associated with AD. But other studies have shown that plasma clusterin levels were not related to Alzheimer’s disease or presymptomatic AD. Hence the diagnostic value of plasma clusterin is still not conclusive. METHODS: Neuropsychological assessment, MRI brain, FDG-PET brain and CSF biomarkers of AD were used for establishing the diagnosis of MCI, AD or Vascular dementia. The CSF control group included patients who were having knee or hip surgery and plasma control group included the spouses of patients. RESULTS: Forty-six patients who gave consent for CSF examination and FDG PET brain were included in the study along with 19 control samples. Alzheimer’s group had 34 patients and Vascular group had 12 patients. Both had a significantly lower value of clusterin than the control samples (p<0.01). The median plasma clusterin level was 84.38 μg/ml in control group, 57.98μg/ml in Alzheimer’s group and 49.93μg/ml in the vascular group. Alzheimer and Vascular group did not differ in plasma clusterin levels. Moreover there was no correlation of plasma clusterin with AD severity. The sensitivity and specificity of plasma clusterin was low for any significance for clinical use. CONCLUSION: Our pilot study shows that plasma clusterin is lower in Alzheimer’s disease with respect to control population. Plasma clusterin levels and severity of Alzheimer’s disease had no significant correlation. There was no difference in plasma clusterin between Alzheimer’s disease and Vascular Dementia. The sensitivity and specificity of plasma clusterin is low for any use in clinical practice. More studies are required to ascertain the utility of plasma clusterin as a biomarker in Alzheimer’s disease.